466 Robust Model of Microglia Replacement With Circulation-Derived Microglia-Like Cells (CDMCs) in CNS Malignancies. (April 2023) - Rodrigues, Adrian; Mader, Marius; Chernikova, Sophia; Li, Guan; Wang, Yuelong; Wong, Sam; Petritsch, Claudia; Wernig, Marius; Gephart, Melanie Hayden
Abstract : INTRODUCTION: Tumor-associated microglia and macrophages (TAMs) represent a main cell type of brain malignancies and demonstrate complex interactions with cancerous cells and the tumor microenvironment. These interactions have important implications for the progression and treatment of malignant central nervous system (CNS) tumors. TAMs have therefore emerged as therapeutic targets, though their potential to date has been unfulfilled. METHODS: C57BL/6 mice were preconditioned for BMT with retroorbital busulfan injections (25 mg/kg), and native microglia were depleted via PLX5622 (1200 mg/kg, chow). Following transplantation, animals underwent intracranial stereotactic injection of syngeneic cell lines of either high-grade glioma (GL261) or breast cancer metastasis (E0771). Following animal sacrifice, we used single cell RNA sequencing of CD45-positive cells to profile the transcriptomic identity of glioma tumor-associated CDMCs (TA-CDMCs). RESULTS: Lineage tracing proved high intra- and peri-tumoral chimerism of BMT-graft derived cells among CNS myeloid cells in both models two weeks after tumor cell injection, demonstrating a robust ability to modify the tumor-immune microenvironment in animal models. TA-CDMCs showed a similarly activated morphology as naÏve TAMs under immunohistochemistry. Pathway enrichment analysis revealed an upregulation of immune response pathways in TA-CDMCs compared to regular TAMs, including the overexpression of genes relevant for the regulation of T cell activation, suggesting possible modification of the glioma immune-environment following CDMC repopulation. CONCLUSIONS: The present study offered a robust proof-of-concept that highly efficient TAM replacement could be achieved in orthotopic murine brain tumor models. Additionally, it appears that replaced CDMCs retain unique transcriptional patterns in the tumor-immune microenvironment, with the upregulation of several key immune response pathways. These efforts may represent a novel route of tumor-directed immunotherapy and offer exciting opportunities for ex-vivo CDMC manipulation to specifically target neoplastic cells.